Cash transfers, poverty, and inequality in Latin America and the Caribbean - Marco Stampini; Nadin Medellín; Pablo Ibarrarán (Inter-American Development Bank (IDB), 2023)
We assess the non-contributory cash transfer systems in 17 Latin American and Caribbean countries to identify factors that keep them from reducing poverty and inequality. To perform this assessment, we analyze three dimensions of size (number of beneficiaries, size of transfer per beneficiary, and size of total budget) and three dimensions of targeting (coverage, leakage, and quality of demographic targeting). We identify 67 programs, which fall into three broad categories: conditional cash transfers, non-contributory pensions, and other transfers. We use an international poverty line of 6.85 dollars PPP per day (similar to the average national poverty line of upper middle-income countries) and adjust survey weights to correct for the fact that household survey data often underestimates the official number of transfer beneficiaries compared to administrative sources. We show that two key factors limit the effect of cash transfer programs on poverty and inequality: the small size of their transfers and their historic under-coverage of the population living in poverty. Transfers represent approximately 33% of the poverty gap. Additionally, only 55% of the population in poverty benefits from these programs. Forty-one percent of people living in households that receive at least one non-contributory transfer are above the poverty line. Children and Indigenous people are underrepresented, relative to their poverty rate, in the rosters of beneficiaries. Brazil, Suriname, Argentina, Chile, Costa Rica, Panama, and Uruguay consistently earn the highest scores across the assessment categories. Our policy recommendations include: (i) intensifying efforts to increase coverage among the poor, using modern poverty mapping techniques along with active, on-the-ground searches and (ii) recertifying eligibility for transfer programs more frequently by using highly interoperable administrative data and social registries. Both efforts are needed to create more efficient income protection systems that address both structural and transient poverty.
Keywords: I38; H53; 330; cash transfer programs; conditional cash transfers; non-contributory pensions; coverage; leakage; targeting; social protection; Latin America and the Caribbean